Edukasi Literasi Perbankan Syariah kepada Anak Usia Dini di Taman Kanak-Kanak Tarbiyatul Athfal Gampong Blang Crum Kandang Kecamatan Muara Dua Lhokseumawe - Hidayatina, Hidayatina; Mardhiah, Ainun; Khairina, Khalish (LSM Catimore dan Sahabat, 2024)
In order to instill the virtue of frugal living, it is imperative to educate children on the practice of saving from an early age. Sharia-compliant banks offer a secure platform for savings. A recent educational initiative undertaken at Tarbiyatul Athfal Kindergarten, Lhokseumawe, on Thursday, July 11, 2024, using an interactive lecture approach to impart a comprehensive understanding of Sharia banking and its associated terms to young children. This program effectively equipped the children with a sound grasp of Sharia banking, as evidenced by their successful responses during the evaluation phase